2012
DOI: 10.1007/s10096-012-1659-x
|View full text |Cite
|
Sign up to set email alerts
|

The microbiology of endophthalmitis: global trends and a local perspective

Abstract: Endophthalmitis is a rare but frequently devastating infection, caused by diverse organisms, including bacteria, viruses, fungi, and parasites. The causative agents of endophthalmitis vary according to the mechanism. The involvement of intraocular structures can result from exogenous spread from ocular trauma, infection of adjacent structures, or as a complication of intraocular surgery. Of the causes of exogenous endophthalmitis, post-operative endophthalmitis is the most frequently encountered; specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
77
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 52 publications
0
77
0
5
Order By: Relevance
“…Exogenous endophthalmitis infection results from an exterior breach of the globe caused either through surgery (postoperative), trauma (posttraumatic), or by fulminant progression of keratitis or scleritis. Since millions of cataract surgeries are performed worldwide (3), postoperative endophthalmitis (POE) is the most frequently encountered exogenous infection (4). On the contrary, endogenous endophthalmitis (EE), which is less common (4), results from the metastasis of bacteria into the eye from a distant infection site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous endophthalmitis infection results from an exterior breach of the globe caused either through surgery (postoperative), trauma (posttraumatic), or by fulminant progression of keratitis or scleritis. Since millions of cataract surgeries are performed worldwide (3), postoperative endophthalmitis (POE) is the most frequently encountered exogenous infection (4). On the contrary, endogenous endophthalmitis (EE), which is less common (4), results from the metastasis of bacteria into the eye from a distant infection site.…”
mentioning
confidence: 99%
“…Since millions of cataract surgeries are performed worldwide (3), postoperative endophthalmitis (POE) is the most frequently encountered exogenous infection (4). On the contrary, endogenous endophthalmitis (EE), which is less common (4), results from the metastasis of bacteria into the eye from a distant infection site. Thus, endophthalmitis needs timely therapy to control the infection and to minimize ocular morbidity.…”
mentioning
confidence: 99%
“…The organism profile was comparable to other published reports. 1, [6][7][8][9] As postoperative endophthalmitis is a devastating complication of cataract extraction operations, numerous studies have been carried out to examine the factors that could reduce its incidence. In the European Society of Cataract and Refractive Surgeons (ESCRS) endophthalmitis study, 10 the authors concluded that the use of intracameral cefuroxime at the end of surgery would significantly reduce the occurrence of postoperative endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous endophthalmitis is most frequently post-operative (keratoplasty); endogenous endophthalmitis, caused by the hematogenous spread of organisms from a remote infectious site into the eye, accounts for 2-15 % of all cases. The most important component of treatment is the intravitreal injection of antibiotics, along with vitrectomy in severe cases[49].…”
mentioning
confidence: 99%